Near-zero sintering shrinkage in pottery with wollastonite addition. Issue 2 (February 2023) - Hao, Dong; Akatsu, Takashi; Kamochi, Nobuaki; Inada, Miki; Shiraishi, Atsunori
Abstract: The precise control of the geometry of pottery is a challenge owing to the undesirable shrinkage and deformation observed after firing. In this study, near-zero sintering shrinkage pottery (NZS) with the sintering shrinkage (SS) of < 2.0% and pyroplastic deformation index (PI) of < 1.5 × 10 −6 mm −1 was developed with varying amounts of added alumina and wollastonite. Wollastonite promotes anorthite crystallisation, thereby preventing sintering shrinkage at ∼1200 °C. The mechanism for the suppressed liquid-phase sintering of the pottery was also analysed. Moreover, NZS were obtained after firing at 1300 °C with a specific phase composition for suppressing the pyroplastic deformation. Thus, NZS was successfully prepared through liquid sintering from natural minerals. Therefore, this study provides a guide for the fabrication of earthenware, stoneware, unglazed porcelain and ceramic tiles with precise dimension and geometry. Additionally, it is also important for reducing the production loss in huge pottery and large-scale production by countering the sintering shrinkage.